Recombined humanized endostatin‐induced suppression of HMGB1 expression inhibits proliferation of NSCLC cancer cells - Fan‐Jie Meng; Shuo Wang; Yi‐Jie Yan; Chun‐Yang Wang; Zhi‐Yu Guan; Jun Zhang (Thoracic Cancer, 2019)
Background Recombined humanized endostatin (Rh‐endostatin) exhibits a potent anti‐cancer effect involving multiple molecular targets and signaling pathways. HMGB1 is a highly conserved DNA‐binding protein involved in cancer development. The therapeutic effect of Rh‐endostatin on HMGB1 has not been reported, thus we investigate the effect in non‐small cell lung cancer (NSCLC) cells. Methods Quantitative real‐time PCR and Western blot were used to analyze the messenger RNA and protein expression of HMGB1 in A549 cancer cells, while enzyme‐linked immunosorbent assay was used to detect the release of HMGB1. Western blot was performed to evaluate HMGB1 expression in SK‐MES‐1 and H661 NSCLC cells. Results Rh‐endostatin inhibited the proliferation of A549 cancer cells and distinctly downregulated the expression and release of HMGB1 in dose and time dependent manners. Rh‐endostatin‐induced HMGB1 downregulation was confirmed in different types of NSCLC cells. Conclusion These results demonstrate the general phenomenon that Rh‐endostatin can induce HMGB1 suppression in a variety of NSCLC cells. Rh‐endostatin may suppress HMGB1 expression and release in A549 cancer cells, thus inhibiting cell proliferation.